Characterizing light attenuation within Northwest Florida Estuaries: Implications for RESTORE Act water quality monitoring. Issue 2 (30th January 2017) - Conmy, Robyn N.; Schaeffer, Blake A.; Schubauer-Berigan, Joseph; Aukamp, Jessica; Duffy, Allyn; Lehrter, John C.; Greene, Richard M.
Abstract: Water Quality (WQ) condition is based on ecosystem stressor indicators (e.g. water clarity) which are biogeochemically important and critical when considering the Deepwater Horizon oil spill restoration efforts under the 2012 RESTORE Act. Nearly all of the proposed RESTORE projects list restoring WC as a goal, but 90% neglect water clarity. Here, dynamics of optical constituents impacting clarity are presented from a 2009–2011 study within Pensacola, Choctawhatchee, St. Andrew and St. Joseph estuaries (targeted RESTORE sites) in Northwest Florida. Phytoplankton were the smallest contribution to total absorption (at-w PAR) at 412 nm (5–11%), whereas colored dissolved organic matter was the largest (61–79%). Estuarine at-w PAR was significantly related to light attenuation (Kd PAR), where individual contributors to clarity and the influence of climatic events were discerned. Provided are conversion equations demonstrating interoperability of clarity indicators between traditional State-measured WQ measures (e.g. secchi disc), optical constituents, and even satellite remote sensing for obtaining baseline assessments. Highlights: Optical Water Quality parameters offer value to RESTORE Act monitoring efforts. Absorption coefficients at 412 nm and integrated over PAR are interoperable. Proxy-IOPs and absorption coefficients are well correlated in NW Florida estuaries. Total absorption coefficient allows for discerning root causes to light attenuation.